The Efect Use of The Two Stay Two Stray Learning Strategy on Students' Learning Outcomes in Al-Qur'an-Hadis Subjects - Karman, Karman; Maslani, Maslani; As-Sa'diyah, Millah Maryam (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
Learning activities that build student activity and produce good learning outcomes depend on the use of learning models that are relevant to student needs. It turns out that the learning method using discussion is not enough to build student activity. This research aims to analyze the Two Stay Two Stray learning strategy on student learning outcomes in Al-Qur'an-Hadith subjects as an alternative to using the discussion learning method. The research was carried out at the Sukamiskin Islamic Boarding School Education Foundation, Bandung using a quantitative approach through the method quasi experiment. The research results show that the application of the Two Stay Two Stray learning strategy has a positive and significant effect on student learning outcomes with an average pre-test score of 60.97 and an average post-test score of 74.19. These results show that the application of the Two Stay Two Stray learning strategy can be used in other subjects.